Furniture design: application of the semantic differential technique to measure and evaluate consumer perception - Shanat, M.B.H; Beale, P. (Universiti Malaysia Sarawak, (UNIMAS), 2010)
This research will investigate the differences in furniture perceptions of form, utility and aesthetic among designers and users. The exploration will search the values of a ‘systematic’ approach to furniture design with ongoing user feedback, which should enhance the acceptability of the design object in the industry. There are 2 types of research frameworks involved which are ‘a systematic design processes' (follows the more or less conventional design process) and the ‘semantic differential’ approaches. The semantic differential questionnaires will be applied to examine perceptions of two subject groups in furniture design. The implications of differences in preference and the relationship between image-word and actual design elements for the subject group will support designers in the control of furniture style for the intended end users.